Pengaruh Media Google Form terhadap Motivasi Belajar Siswa SMKN 71 Jakarta - Ramadhan, Syahrul Gio; Sulthani, Dinil Abrar (Universitas Batanghari Jambi, 2023)
The use of practical and efficient learning media is still rarely used in learning, giving rise to a less active and passive learning atmosphere at SMKN 71 Jakarta, therefore these problems can be overcome with Google form media. The purpose of this study was to analyze and find out whether there is an influence of Google Form media on student learning motivation and to calculate how much influence Google Form media has on student learning motivation. This research method is a correlational method that is used to measure whether there is a relationship and influence between the x and y variables and then a significance test is carried out. The results of this study are that there is an influence of Google Form media on student learning motivation with the results of the correlation that has been analyzed which is equal to 0.545 while the results of the significance test are positive and significant. The conclusion of this study is that there is an influence of Google Form media on students' learning motivation in the moderate category as well as positive and significant.